EKSPLORASI MOTION GRAPHICS SEBAGAI ALAT NARATIF PADA KARYA DOKUMENTER USAI MERDEKA - Tegar, M. Farhan Putra; Astuti, Aprilina Dwi; Hakim, Herry Abdul (CENDEKIA: Jurnal Ilmu Pengetahuan, 2025)
This study aims to explore the type of motion graphics that are suitable as narrative reinforcement in the documentary work After Independence. The documentary work After Independence is a documentary that explains the mining of limestone mountains in the karst landscape of Mount Sewu and its relationship with nature. The use of motion graphics in this documentary helps illustrate visual explanations so that they are easily understood by users. The selection of motion graphics techniques also strengthens the message conveyed in this documentary work. This study uses a qualitative descriptive method, the research process goes through three stages: pre-production, production and post-production. The motion graphics techniques applied include animation techniques, map animation graphics and easing. The results of the study Animation techniques successfully create visual information that is easy to digest and interesting, applied with text animator, path animation, and parent. The easing technique produces flexible movement of graphic elements and gets a realistic impression in a movement according to real-world conditions whose application uses a graph editor by adjusting the ease curve to determine the initial and final speed of a movement. Map animation graphic technique is applied to help visualize geographic statistical data into an attractive and easier to understand map visual, implemented by animating geographic maps combined with geographic data in the form of geoshape files applied using the GEOlayer3 plug-in. By exploring motion graphics, a documentary work is produced with attractive, informative and easy to digest data visualization. ABSTRAK Penelitian ini bertujuan mengeksplorasi jenis motion graphyc yang sesuai sebagai penguat naratif  pada karya dokumenter Usai Merdeka.  Karya dokumenter Usai Merdeka merupakan sebuah dokumenter yang menjelaskan tentang penambangan gunung kapur pada bentang alam karst gunung sewu dan hubungannya dengan alam. Penggunaan motion graphyc pada karya dokumenter  ini membantu mengilustrasikan penjelasan visual agar  mudah dipahami oleh pengguna.  Pemilihan teknik  motion graphyc turut serta memperkuat pesan yang disampaikan pada karya dokumenter ini. Penelitian ini menggunakan metode diskriptif kualitatif, proses penelitian melalui tiga tahapan yaitu pra produksi, produksi dan pasca produksi. Teknik motion graphyc yang diterapkan meliputi  teknik animation, map animation graphic dan easing. Hasil dari penelitian Teknik animation berhasil menciptakan visual informasi yang mudah dicerna dan menarik,  diterapkan dengan  text animator, path animation, dan parent. Teknik easing menghasilkan  pergerakan elemen grafis yang lentur dan  mendapatkan kesan realistis dalam sebuah pergerakan sesuai pada kondisi di dunia nyata yang penerapannya menggunakan graph editor dengan mengatur kurva ease untuk menentukan kecepatan awal dan akhir suatu gerakan. Teknik map animation graphic diterapkan untuk membantu memvisualisasikan data statistik geografis menjadi visual peta yang menarik dan lebih mudah dipahami, diterapkan dengan  menganimasikan peta geografis yang digabungkan data geografis berupa geoshape file diaplikasikan  menggunakan plug-in GEOlayer3. Dengan mengeksplorasi motion graphyc dihasilkan sebuah karya dokumenter dengan visualisasi data yang menarik, informatif dan mudah dicerna.